Thermo-responsive microgels based on encapsulated carbon quantum dots - Campos, Bruno B. (2017)
In this work carbon quantum dots (CQDs) nanoparticles are synthesized from D-lactose using a hydrothermal method andthen they are coated with polyethyleneglycol (CQDs@PEG).These particles exhibit a monodisperse spherical morphologywith an average particle size of ~4 nm. Nuclear magnetic resonance (NMR) and Fourier transform infrared spectroscopy(FTIR) showed the presence of the hydroxyl groups from the ethylene glycol molecules grafted on the CQDs surface, whichconfirms that PEG was covalently attached to the nanoparticles surface. Fluorescence analysis demonstrates a shift in theemission at 495 nm after PEG coating. Modified carbon dots were introduced into thermo-responsive pNIPAM microgels.The resultant pNIPAM-CQDs@PEG hybrid system exhibits interesting fluorescent properties. Transmission electronmicroscopy (TEM), fluorescence microscopy, and energy-dispersed X-ray (EDX) spectroscopy confirm the incorporation ofCQDs particles into the microgels. Finally, dynamic light scattering (DLS) analysis confirms that the further hybrid microgelsbased in pNIPAM are thermo-responsive, with a transition temperature similar to that for a system with an ioniccomponent.